Nutritional status and quality of life in adults and older adults with depression - Godoy, Aline Rodrigues (2019)
Objective: To assess nutritional status and quality of life in adults and older adults with and without depression. Methods: This is a quantitative cross-sectional study of 79 users of Primary Health Care Centers located in the municipalities in the Vale do Taquari, Rio Grande do Sul. To determine the scores of the Quality of Life (QoL) domains (physical, psychological, environmental and social) we used the World Health Organization Quality of Life-Bref questionnaire and a socioeconomic questionnaire (age, income, education and marital status). Anthropometric measurement included weight, height, Body Mass Index, Waist Circumference (WC) and Neck Circumference (NC). Diagnosis of depression was given by psychologists. The maximum significance level assumed was 5% (p≤0.05) and the analysis was performed using SPSS version 22.0. The Mann-Whitney test, the Pearson’s correlation coefficient and the Chi-squared test were used. Results: There was a direct correlation between age and the physical (p=0.017), psychological (p